Quantum Entanglement Between Charge Qubit and Mechanical Cat-States in Nanoelectromechanical System - Matija Tečer; Danko Radić (Mathematics, 2025)
We present a detailed mathematical description, both an analytical model and a numerical simulation, of a physical system based on a superconducting nanoelectromechanical setup that generates nanomechanical cat-states entangled with charge qubit states. The system consists of a superconducting grain in a regime of the Cooper pair box (the charge qubit) that performs mechanical vibrations between two bulk superconductors. Operation of the device is based on the AC Josephson effect, i.e., the phase difference between superconducting electrodes is controlled by a DC bias voltage following the operational switch on/off protocol. We compare an analytical idealised solution with numerical simulation using experimentally feasible parameters, different decoherence processes, as well as imperfections of experimental procedures such as time-control of the bias voltage, to get insight into how they influence the time-evolution of the realistic system, deteriorate the quantum coherence, and affect the formation of the cat-states.